How does the spatial context shape conditions for car dependency? An analysis of the differences between and within regions in the Netherlands - Wiersma, Jake; Bertolini, Luca; Straatemeier, Thomas (Journal of Transport and Land Use, 2015)
Adapting cities and region to facilitate car use is not only a technical issue. It has made society heavily car-dependent, increasing the vulnerability of society to adverse changes in social, economic, environmental, or other spheres. This paper analyzes how the spatial context shapes conditions for car dependency, specifically focusing on the case of the Netherlands. Our research shows that, except in the periphery of the country, most daily amenities are within walking or biking distance, both in cities as well as in suburban and rural areas. However, regarding accessibility to jobs, there is no competitive alternative to the car—even in central city areas, which provide many more travel choices. The differences are not only related to population density or land use within the city, as is often thought, but also to the position of the urban area in the regional spatial context (i.e., its location relative to other urban areas). The bicycle as an alternative transport mode to the car scores highest in monocentric urban regions and in the central areas of cities close to a coastline or a national border. Public transport scores highest in central areas of medium-sized cities in polycentric regions and satellite towns near big cities.